(untitled) (Studia austriaca, 2020)
The study of literature should not be based only on a one-sided analysis of the text, it should also take account of the perspective of the reader. Considering the connection between literature and recipient, there are structures that influence cognitive perception during reading. Thus the spatial order of the story, dedicated to cognitive poetics, is very important. The article focuses on the literary mechanisms of spatial perception and spatial concepts in narration, especially in the early work of the Austrian poet and novelist Ilse Aichinger.